Profiles of Mathematics Performance by Students of Chilean City Schools, Based on Cognitive Ability by Socioeconomic Level - Mario Tirso Oscar Baltra San Martín (Universidad Autónoma de Baja California, 2010)
This study analyzes the performance profile of Chilean city-school students from different socioeconomic strata, in relation to different sets of cognitive abilities specified in the curriculum framework for mathematics education in their country. The study is correlational and ex post facto in type, derived from the results of the math test of the System for Measuring Educational Quality (SIMCE) applied to second-semester students of the 2001 school year. The percentage of students at each performance level was calculated, based on each student's probability of correctly answering each of the test questions, using logistic function, associated with the two-parameter model of the Item Response Theory (IRT). The results show that regardless of the set of cognitive abilities in question, the performance profile follows a similar pattern. It was found that in general, there is a linear decrease in the percentage of those who achieve superior performances among students from low and medium-low strata, and exponential increases for middle-class students.